2015
DOI: 10.1093/nar/gkv591
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin and extracellular vesicle associated sperm RNAs

Abstract: A diverse pool of RNAs remain encapsulated within the transcriptionally silent spermatozoon despite the dramatic reduction in cellular and nuclear volume following cytoplasm/nucleoplasm expulsion. The impact of this pronounced restructuring on the distribution of transcripts inside the sperm essentially remains unknown. To define their compartmentalization, total RNA >100 nt was extracted from sonicated (SS) mouse spermatozoa and detergent demembranated sucrose gradient fractionated (Cs/Tx) sperm heads. Sperm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 72 publications
(91 reference statements)
1
53
0
Order By: Relevance
“…Sperm maturation takes between 70 and 100 days in humans, predominantly in the seminiferous tubules that are in constant contact with supporting Sertoli cells. This is followed by a 1-2 week transitional period in the epididymis, during which time proteins and a small amount of RNA are selectively shuttled into the developing sperm 51,52 . The paternal preconception environment modulates the RNA content of the developing sperm, with possible effects on post-fertilization development and offspring phenotypes 53 .…”
Section: Mechanisms Involving Parental Gametesmentioning
confidence: 99%
“…Sperm maturation takes between 70 and 100 days in humans, predominantly in the seminiferous tubules that are in constant contact with supporting Sertoli cells. This is followed by a 1-2 week transitional period in the epididymis, during which time proteins and a small amount of RNA are selectively shuttled into the developing sperm 51,52 . The paternal preconception environment modulates the RNA content of the developing sperm, with possible effects on post-fertilization development and offspring phenotypes 53 .…”
Section: Mechanisms Involving Parental Gametesmentioning
confidence: 99%
“…Moreover, Nixon et al (2015a,b) showed that also the miRNA profile of mouse spermatozoa changes during epididymal transit from caput to cauda, and in a study by Johnson et al (2015), long (>100 nt) RNA content of spermatozoa was shown to comprise extracellular-vesicle-associated RNA, possibly incorporated into spermatozoa during epididymal transit.…”
Section: R96 P Sipilä and I Björkgrenmentioning
confidence: 99%
“…These examples of potent bioactivity and the biocompatible nature of EVs have inspired the development of vesicles as vehicles for both drug and gene therapy delivery for a large number of applications [23]. EVs may even play a direct role in evolution as studies show EV-mediated transfer of nucleic acids into sperm cells [24]. Final evidence for the importance of EVs is given by their existence across taxonomic kingdoms, from archaea through bacteria to plants and animals [1].…”
Section: Introductionmentioning
confidence: 99%